2010
DOI: 10.1007/s10641-010-9585-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two Synodontis (Siluriformes: Mochokidae) catfish species in the White Nile and Lake Nubia

Abstract: I found that cluster analysis of body weight, 25 morphometric measurements and seven meristic counts separated most of the population of Synodontis schall, from the Jebel Aulia area, Khartoum along the White Nile, from the population of Lake Nubia, the southern part of a large reservoir on the River Nile at the northern borders of the Sudan, above the Aswan High Dam in Egypt. Analysis of variance revealed significantly higher mean numbers of gill rakers and mandibular teeth in Lake Nubia for S. schall and S. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
3
1
0
Order By: Relevance
“…It was observed that some metric features were constant such as pelvic fin spine, dorsal fin spine while others varied. The finding was in line with the work of Mohamed (2010) who recorded similar metric features with S. schall and S. serrate. The variation observed in this study when compared with other species might be related to environmental variations such as water temperature, stress, food availability, spawning ground and sex.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was observed that some metric features were constant such as pelvic fin spine, dorsal fin spine while others varied. The finding was in line with the work of Mohamed (2010) who recorded similar metric features with S. schall and S. serrate. The variation observed in this study when compared with other species might be related to environmental variations such as water temperature, stress, food availability, spawning ground and sex.…”
Section: Discussionsupporting
confidence: 92%
“…The morphometric (total length, standard length, body depth, head length, head depth, snout length, dorsal fin length, anal fin length, eye diameter, body weight, caudal peduncle length, caudal peduncle depth, caudal peduncle depth, pelvic fin length) features of S. omais were within the range reported by Famoofo and Abdul (2020) from Iwopin freshwater ecotype of Lekki Lagoon, Ogun State, Nigeria who worked on S. nigrita. The result from morphometric characteristics was also found to be similar to the study of Mohamed (2010) who studied the characteristics of two Synodontis species in the White Nile and Lake Nubia in Sudan. The meristic (dorsal fin ray, anal fin ray, pectoral fin ray, caudal fin ray, pelvic fin ray, pelvic fin spine, dorsal fin spine and gill rakers) features which are countable features are also used for fish identification.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Synodontis schall is traditionally considered widespread throughout the Nilo-Sudanian ichthyological province from the Atlantic to Indian Ocean 17 . Its widespread distribution, abundance and easy harvesting make it one of the most important subsistence fish species in Sub-Saharan Africa north of equator and along the whole Nile valley 28,32–34 . Importantly, this ecologically plastic species 28 is less likely to be affected by climatic changes and anthropogenic drainage alterations, making it a prospective source for fisheries in the future 35 .…”
Section: Methodsmentioning
confidence: 99%